Walkmeter as an alternative method to enhance elementary school students ability in solving velocity and acceleration problems - Akmar, Norfaridatul (Education and Development Research, 2024)
Understanding physics relies heavily on mastering mathematical formulas, essential for problem-solving, critical thinking, reasoning, and communication. Yet, students struggle due to uninspiring explanations, leading to lost focus during learning. One such topic that involves mathematical formulas in physics is velocity and acceleration. This study aims to assist physics students from Sekolah Menengah Kebangsaan Putrajaya Presint 16(1), Malaysia who have difficulties in solving velocity and acceleration drill questions by using the Walkmeter application for learning. This approach also aims to improve and enhance the teaching practices of the teacher and increase students' interest and achievement in solving velocity and acceleration questions. Initial observations during the teaching and learning process showed that there were students who were unclear and took a long time to master the velocity and acceleration drill exercises. Initial surveys through observations, document analysis, and questionnaires indicated that students easily lose focus. The difficulty in remembering formulas and the conventional methods that are not suitable caused students to take a long time to solve drill questions. An action plan was devised by developing the WalkMeter application outside the classroom. Information gathered from observations and questionnaires showed an improvement in students' interest, attitudes, and achievements after using the WalkMeter application. Overall, this study has successfully enhanced the quality of teaching by teachers and the learning experiences of students in solving velocity and acceleration drill questions more easily and effectively. This has made the out-of-classroom teaching and learning process more meaningful.